2022
DOI: 10.3390/app12052277
|View full text |Cite
|
Sign up to set email alerts
|

Catchment Soil Properties Affect Metal(loid) Enrichment in Reservoir Sediments of German Low Mountain Regions

Abstract: Sediment management is a fundamental part of reservoir operation, but it is often complicated by metal(loid) enrichment in sediments. Knowledge concerning the sources of potential contaminants is therefore of important significance. To address this issue, the concentrations and the mobile fractions of metal(loid)s were determined in the sediments and the respective catchment areas of six reservoirs. The results indicate that reservoirs generally have a high potential for contaminated sediment accumulation due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The variability coefficient of sandstone exceeds 0.5, indicating high variability, whereas the variability coefficients of the other parent rocks are all below 0.5, indicating moderate variability. Single-factor variance analysis revealed that mudstone had the most significant impact on soil Pb content, primarily because of the distinct differences in mineral composition among different rock types, leading to element enrichment or leaching during soil formation (Hahn et al, 2022).…”
Section: Influence Of Parent Rock Typesmentioning
confidence: 99%
“…The variability coefficient of sandstone exceeds 0.5, indicating high variability, whereas the variability coefficients of the other parent rocks are all below 0.5, indicating moderate variability. Single-factor variance analysis revealed that mudstone had the most significant impact on soil Pb content, primarily because of the distinct differences in mineral composition among different rock types, leading to element enrichment or leaching during soil formation (Hahn et al, 2022).…”
Section: Influence Of Parent Rock Typesmentioning
confidence: 99%
“…In general, the concentrations found for the three toxic metals (Al, Cd, and Pb) were always highest in vegetable soups, followed by poultry and meat soups, because soil is a natural reservoir of contaminants, such as these three metals [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Te abovementioned approaches do not always take into account the potential remobilization of metal(loid)s in alluvial soils and the translocation of sediment particles. Many studies have shown that river basins/reservoirs generally have a high potential for contaminated sediment accumulation due to preferential deposition of fne particles (e.g., [29]). However, rivers are dynamic systems, in which sediment particles and their associated contamination are moved, and can be considered both a sink and a source of (contaminated) sediments.…”
Section: Previous Research On Alluvial Soils In Relation To Pollutionmentioning
confidence: 99%